Transformed ALDH2−/− hepatocytes by ethanol could serve as a useful tool for studying alcoholic hepatocarcinogenesis. (January 2021) - Zhang, Xiu-Ning; Meng, Fan-Ge; Wang, Yi-Ran; Liu, Shi-Xuan; Zeng, Tao
Abstract: Alcohol is a well-recognized hepatic carcinogen. Alcohol is metabolized into genotoxic acetaldehyde in hepatocytes, which is catalyzed by aldehyde dehydrogenase 2 (ALDH2). The detailed underlying mechanisms of alcohol-related hepatocellular carcinoma (HCC) remains unclear, at least partially, due to the absence of appropriate experimental models. Current studies suggest that rodents are not good models of the most common liver diseases that trigger HCC including alcoholic liver injury. We hypothesize that ethanol could induce transformation of immortalized normal liver cells, which may serve as a versatile tool for studying alcoholic HCC. Besides, we believe that knockout of ALDH2 will help to shorten the time course of transformation, as ALDH2 deficiency will significantly increase the accumulation of acetaldehyde in hepatocytes. Using this model, the dynamic changes of carcinogenesis-related molecular events could be easily examined. Furthermore, the transformed cells isolated from soft agar could be inoculated to mice for studying invasion, metastasis, and also for screening prophylactics.